Imperial Debris: Reflections on the Lisbon Cityscape in Contemporary Portuguese Fiction - Martinho Ferreira, Patrícia (Journal of Lusophone studies, 2020)
This essay focuses on the literary image of contemporary Lisbon. Through an analysis of the anthology Lisbon Tales and Trails (2017) and Djaimilia Pereira de Almeida’s Luanda, Lisboa, Paraíso (2018), I examine how Lisbon’s representation on a global stage exposes the complexities and ambiguities of a metropolitan area deeply connected to the legacies of empire. Moving through fictional texts from the city center to the suburban periphery, I offer a focused reflection on Lisbon’s postcolonial/post-imperial ethnoscape.